Static and dynamic flow maps: Comparing the usability between impaired color vision and normal color vision - Amorim, Fabrício Rosa [UNESP]; Pugliesi, Edmur Azevedo [UNESP] (FapUNIFESP (SciELO), 2021)
Flow maps represent data over time that connect different locations. A cartographic representation for different vehicle’s flows with color hue variation, ideally, could be well succeed for users having Normal Color Vision (NCV) or having Color Vision Deficiency (CVD). The scientific research about reading flow maps by people having NCV or CVD is not clearly established, mainly when considering the perceptual properties present in the static and dynamic visual variables. This work aims to evaluate and compare the usability (effectiveness, efficiency, and satisfaction) of static and dynamic flow maps reading which were represented by using ordered hues, with 10 people having CVD and with 10 people having NCV. An area located in the city of Presidente Prudente, state of São Paulo, was selected to design eight static maps and eight dynamic maps at 1:5,000 scale. In an experiment conducted in laboratory, the participant’s tasks were select and draw routes between origin and destination places shown on maps. The maps were displayed individually in a tablet with a size of 7 inches, and each task lasted up to 30 seconds. The results showed that the efficacy was similar between the NCV and CVD participants when they were using static or dynamic maps. Higher efficiency was found with the use of dynamic maps among participants having NCV, and higher efficiency was found with the use of static maps among participants having CVD. Additionally, dynamic maps showed a higher level of satisfaction than static maps for groups of NCV and CVD. Different kinds of static and dynamic visual variables can be considered as matter of investigation for future research to represent flow of vehicle in the cities, especially for CVD.
Mapas de fluxo estáticos e dinâmicos: Comparando a usabilidade entre a visão impedida de cores e a visão normal de cores
Keywords: Color blindness; Static and Dynamic Symbols; Usability; Vehicle Flow Maps; Visual perception